The role of peers in estimating tenure-performance profiles: Evidence from personnel data - Andries de Grip; Jan Sauermann; Inge Sieben (Institute for the Study of Labor (IZA), 2011)
In this paper, we estimate tenure-performance profiles using unique panel data that contain detailed information on individual workers' performance. We find that a 10 per cent increase in tenure leads to an increase in performance of 5.5 per cent of a standard deviation. This translates to an average performance increase of about 75 per cent within the first year of the employment relationship. Furthermore, we show that there are peer effects in learning on-the-job: Workers placed in teams with more experienced and thus more productive peers perform significantly better than those placed in teams with less experienced peers. An increase in the average team tenure by one standard deviation leads to an increase of 11 to 14 per cent of a standard deviation in performance.
urn:nbn:de:101:1-201201102958
Keywords: J24; D24; L89; 330; tenure-performance profiles; experience; learning on-the-job; peer effects; productivity; call centres; Arbeitsproduktivität; Soziale Beziehungen; Lernprozess; Callcenter; Niederlande